Analisis Kemampuan Numerasi Mahasiswa Calon Guru Matematika - Novitasari, Dwi; Humaira Salsabila, Nilza; Amrullah, Amrullah; Azmi, Syahrul; Hikmah, Nurul (FKIP Universitas Mataram, 2024)
Preservice mathematics teachers will eventually become mathematics teachers and teach mathematics in schools to students. Therefore, it is important to assess the numeracy skills of preservice mathematics teachers to develop their numeracy skills, which will positively impact students once they start teaching in schools. This study aims to describe the numeracy skills of preservice mathematics teachers about numeracy, including how well they can explore mathematical concepts in problems related to numeracy. This study is a qualitative descriptive. The subjects of this study are 28 mathematics education students from the University of Mataram. The instruments used in this study are questionnaires and tasks containing numeracy problems using the Sasak cultural context. Data analysis employs descriptive qualitative analysis, which includes data transcription, categorization, data presentation, description of the numeracy skills of teacher candidates, and conclusion. The results show that, in general, students have not been able to distinguish between numeracy and mathematics. Additionally, students still face difficulties in designing numeracy-oriented learning, especially using the socio-cultural context